1999
DOI: 10.1590/s0103-84781999000300017
|View full text |Cite
|
Sign up to set email alerts
|

Propagação vegetativa de Platanus AcerIfolia Ait.: (I) efeito de tipos fisiológicos das estacas e épocas de coleta no enraizamento de estacas

Abstract: RESUMO O objetivo desse trabalho foi avaliar os efeitos do tipo fisiológico da estaca e da época de coleta no enraizamento de estacas de SUMMARY The aim of this work was to evaluate the effect of the physiological type of the cutting on rooting of Platanus acerifolia Ait. cuttings collected at different times. The treatments followed a 4 x 4 factorial scheme, involving four physiological types of the cuttings (hardwood, basal semi-herbaceous, middle semiherbaceous, and thin basal semi-herbaceous), and four dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
(2 reference statements)
3
5
1
3
Order By: Relevance
“…However, in the present study, cuttings were collected in August, 2013 which may explain differences in results between two studies. However, these results are comparable in variability to the report by Ono, de Barros & Rodrigues (1994), and Nicoloso, Lazzari & Fortunato (1999), who observed that best cuttings rates were obtained when cuttings were collected during fall season.…”
Section: Discussionsupporting
confidence: 89%
“…However, in the present study, cuttings were collected in August, 2013 which may explain differences in results between two studies. However, these results are comparable in variability to the report by Ono, de Barros & Rodrigues (1994), and Nicoloso, Lazzari & Fortunato (1999), who observed that best cuttings rates were obtained when cuttings were collected during fall season.…”
Section: Discussionsupporting
confidence: 89%
“…S. terebinthifolius was the species that had the highest mean dry weight (Table 5), as a result of higher rates of rooting and the greater number of roots produced by cuttings (Table 3). These results are in agreement with the results by Nicoloso et al (1999) for Platanus acerifolia Ait., who observed that larger diameter cuttings presented a higher number of roots per cutting, therefore, presenting higher root dry matter.…”
Section: Root Dry Weightsupporting
confidence: 93%
“…The application of phytoregulators on species with rooting difficulty can compensate for low levels or even lack of endogenous auxin (WAGNER et al, 1989;PIO et al, 2004). Auxin induces rooting in many species thus providing a higher rate and speed of root formation, and greater quality, uniformity and survival of the root system.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Nicoloso et al (1999) e Hartmann (2011, estacas medianas apresentam maiores teores de carboidratos, quando comparadas a apicais que se correlacionam com maior incremento de raízes de ordem primária. Nicoloso et al (1999) observaram que estacas de Platanus acerifolia Ait, com maiores diâmetros (estacas medianas), obtiveram maiores incrementos de massa seca de raízes de primeira ordem e de segunda ordem, quando comparadas com estacas herbáceas apicais. Tais parâmetros são de grande importância, pois estacas com elevado incremento de raízes apresentam melhor desempenho quando colocadas no campo (NOOR et al, 2009).…”
Section: Resultsunclassified
“…Nicoloso et al (1999) observaram que estacas de Platanus acerifolia Ait, com maiores diâmetros (estacas medianas), obtiveram maiores incrementos de massa seca de raízes de primeira ordem e de segunda ordem, quando comparadas com estacas herbáceas apicais. Tais parâmetros são de grande importância, pois estacas com elevado incremento de raízes apresentam melhor desempenho quando colocadas no campo (NOOR et al, 2009). Nesse contexto, West (2006) destaca que, dentre as diversas funções do sistema radicular das plantas, destacam--se três papéis fundamentais: manter a planta fixa ao substrato (raízes de primeira ordem), absorver água e sais minerais (raízes de segunda ordem) e produzir hormônios reguladores de crescimento.…”
Section: Resultsunclassified